La pedagogía digital, durante la mediación didáctica en el desarrollo de resultados de aprendizaje en los alumnos de sexto año de egb paralelo “C” de la Unidad Educativa Aníbal Salgado Ruiz, del cantón Tisaleo, provincia de Tungurahua, estudio realizado durante los meses de diciembre del 2021 a marzo del 2022 - Aguayza Bermeo, Jimmy Wladimir (2022)
In this final report of the Titling project, which was carried out in the Aníbal Salgado Ruiz Educational Unit, in the Tisaleo canton, province of Tungurahua, this was carried out during the months of December 2021 to March 2022. It was carried out with In order to investigate relevant aspects of digital pedagogy during didactic mediation in the development of learning outcomes in sixth-year students of basic general education parallel "C", we consider it highly relevant to deal with some relevant research on contemporary issues such as the COVID19 pandemic, a situation that affected the entire society and in this way it is possible to make known what measures are being taken in the educational field so that education is not truncated. A data collection instrument was applied, such as the interviews, which were applied to 24 students; therefore, an interpretation could be made of the information acquired. The research finds its own authorship, which we can find in the scientific theory where scientific texts on important topics are written, mentioned by authors who stuck to similar topics and delved into the topic of this experiential work.